Bi-Color LED Sequential Running Light / Noor Rahila Abdul Rahim and Azni Suhalfa Abdul Aziz - Abdul Rahim, Noor Rahila; Abdul Aziz, Azni Suhalfa (2005)
The main of this project is to build Bi-Colour LED Sequential Running Light. The main components that control for LED Sequential Running Light are Timer (IC 555) and Decade Counter (IC CD 4017). The Timer (IC 555) is set to operate in astable mode to provide low frequency clock pulse to the sequential Decade Counter (IC CD 4017). The output of a Decade Counter (IC CD 4017) is changed in a given sequence due to the output pulses of the Timer (IC 555), The circuit also designed by Light Emitting Diode, continently LED for display purposes. LED is a popular electronic light source based on Electro luminescence Different colors of LED are used to show sequential running light that run in directions opposite to each other. The system is mainly for advertising purposes. For example, it can be connected to the speaker and the LED will light up according to the sound level (Music Box) It is also widely used to decorate signboards at restaurants and shops to attract the attention of their customers.